Human Intestinal Organoids: Promise and Challenge - Jasin Taelman; Jasin Taelman; Mònica Diaz; Mònica Diaz; Jordi Guiu; Jordi Guiu (Frontiers in Cell and Developmental Biology, 2022)
The study of human intestinal biology in healthy and diseased conditions has always been challenging. Primary obstacles have included limited tissue accessibility, inadequate in vitro maintenance and ethical constrains. The development of three-dimensional organoid cultures has transformed this entirely. Intestinal organoids are self-organized three-dimensional structures that partially recapitulate the identity, cell heterogeneity and cell behaviour of the original tissue in vitro. This includes the capacity of stem cells to self-renew, as well as to differentiate towards major intestinal lineages. Therefore, over the past decade, the use of human organoid cultures has been instrumental to model human intestinal development, homeostasis, disease, and regeneration. Intestinal organoids can be derived from pluripotent stem cells (PSC) or from adult somatic intestinal stem cells (ISC). Both types of organoid sources harbour their respective strengths and weaknesses. In this mini review, we describe the applications of human intestinal organoids, discussing the differences, advantages, and disadvantages of PSC-derived and ISC-derived organoids.